Estudo de probabilidades de ruptura para fundações profundas executadas em uma obra em Mato Grosso do Sul - Altoé, Brenda da Silva (2018)
This work presents a study about the behaviour continuous helix piles, tested with static loads, which have been executed in an industrial construction in Mato Grosso do Sul. Such study was based on STP field tests, performed on a terrain composed of alluvial sediments, with irregular layers with sandy, silt and loamy composition. The study consists in two approaches, deterministic and probabilistic, being that the deterministic, aims to compare safety factors (FS) estimated by five semi-empirical methods: Aoki-Velloso (1975) - Velloso-Lopes (2002); Aoki- Velloso (1975) modified by Monteiro (1997); Décourt-Quaresma (1978) – Décourt (1996); Alonso (1996) and Antunes-Cabral (1996), with values obtained by extrapolation of the loadsettlement curves, drawn from the static loads, by the methods: Van der Veen (1953); Van der Veen (1953) modified by Aoki (1976) and NBR 6122 (ABNT, 2010). In this field, the mean and standard deviation of the errors of the FS values obtained by semi-empirical methods in relation to the ones obtained via extrapolation are presented. Décourt-Quaresma (1978) – Décourt (1996) method was the most conservator one, presenting the lowest error, both related to the mean and the standard deviation of FS. For analyses with extrapolation, Van de Veen (1953) - Aoki (1976) method was the one that generated the lowest error, both in the mean value of FS and in its standard deviation. The probabilistic analysis took into consideration the soundings with radius of 100m, 150m and 200m around each tested pile, to statistically estimate the values of the mean and the variance of the safety factor in these regions by the semiempirical methods. The Kolgomorov-Smirnov test confirmed Gaussian distribution for the FS, allowing the use of Morlá Catalán and Cornell (1976) methodology to calculate the realiableness indexes and the rupture probabilities. Décourt-Quaresma (1978) – Décourt (1996) method was the most conservator one, with the lowest values and the highest ruin probability. Larger sample sizes not necessarily resulted in more accurate estimates of the FS probability distribution, although in most of the cases the FS error has decreased both in mean and standard deviation with the increase of the sampling area. Besides, the ruin probability tends to be slightly sensitive to variations in the sampling areas.